Tauberian theorems with remainder for (H, p, α, β)-and (C, p, α, β)-methods of summation of functions of two variables - Aldanov, V. M.; Mikhalin, G. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider a general method of obtaining Tauberian theorems with remainder for Hölder- and Cesarotype methods of summation.